Redefining typhoid diagnosis: what would an improved test need to look like?. Issue 5 (31st October 2019) - Mather, Richard G; Hopkins, Heidi; Parry, Christopher M; Dittrich, Sabine
Abstract : Introduction: Typhoid fever is one of the most common bacterial causes of acute febrile illness in the developing world, with an estimated 10.9 million new cases and 116.8 thousand deaths in 2017. Typhoid point-of-care (POC) diagnostic tests are widely used but have poor sensitivity and specificity, resulting in antibiotic overuse that has led to the emergence and spread of multidrug-resistant strains. With recent advances in typhoid surveillance and detection, this is the ideal time to produce a target product profile (TPP) that guides product development and ensure that a next-generation test meets the needs of users in the resource-limited settings where typhoid is endemic. Methods: A structured literature review was conducted to develop a draft TPP for a next-generation typhoid diagnostic test with minimal and optimal desired characteristics for 36 test parameters. The TPP was refined using feedback collected from a Delphi survey of key stakeholders in clinical medicine, microbiology, diagnostics and public and global health. Results: A next-generation typhoid diagnostic test should improve patient management through the diagnosis and treatment of infection with acute Salmonella enterica serovars Typhi or Paratyphi with a sensitivity ≥90% and specificity ≥95%. The test would ideally be used at the lowest level of the healthcare system in settings without a reliable power or water supply and provide results in <15 min at a cost of <US1.00. Conclusion: This report outlines the first comprehensive TPP for typhoid fever and is intended to guide the development of a next-generation typhoid diagnostic test. An accurate POC test will reduce the morbidity and mortality of typhoid fever through rapid diagnosis and treatment and will have the greatest impact in reducing antimicrobial resistance if it is combined with diagnostics for other causes of acute febrile illness in a treatment algorithm.